RISK FACTORS OF SURGICAL SITE INFECTION AT THE REGIONAL AND TEACHING HOSPITAL CENTER OF BORGOU (BENIN) - Adrien, Hodonou M.; S Alexandre, Allode; S Romaric, Tobome; Fanny, Hounkponou-ahouingnan; Holden, Fatigba O; Sambo Bio, Tamou; AD Emile, Mensah; Christelle HE, Bankole; Felix, Atakpa; K. Delphin, Mehinto (International Journal of Clinical and Biomedical Research, 2017)
Introduction: The reduction of the SSI rate requires knowledge of its risk factors. Objective: To analyze the risk factors of SSI occurrence at CHD-B Methods: Prospective, descriptive and analytical study involving 603 patients undergoing general surgery (218) and obstetrics and gynecology (385) from 1st January to 31st July 2013. Results: 44 patients have developed SSI (7.3%). The SSI frequency was 12.8% in general surgery and 4.2% in gynecology-obstetrics (p significant). The mean age of patients developing SSI was 30.7 ± 15.8 years with a minimum and maximum 5 months and 70 years, respectively; and for general surgery patients, there were 23 men and 5 women (p not significant). The presence of preoperative infectious spot at admission (P = 0.003), the preoperative shaving of the site to be incised (p = 0.000), the ASA score (p = 0.000), the surgery contamination class (p = 0.000), and the NNIS score (p = 0.000) were all significantly related to SSI occurrence. Considering all these factors, the NNIS score ≥2 remained the predictive tool by multiplying by 3.4 the risk of SSI occurrence. Conclusion: NNIS score is the best SSI prediction tool at CHD-B. KEYWORDS: Surgical site infection; Risk factor; NNIS score.